Ingreso promedio de los habitantes de la ciudad de Loja en el periodo 2014 y su incidencia en el acceso a la canasta básica - Ordóñez Vivanco, Claudia Roxana (2015)
The analysis of the income earned by residents of the city of Loja, is an important diagnosis, both in the economic field and in the social aspect, to know objectively whether the wages paid to household members of our city will It lets enjoy satisfactory levels of well-being through access to assets that make up the basic food basket. By the above it has been proposed this research called "average income of the inhabitants of the city of Loja IN THE PERIOD 2014 AND ITS IMPACT ON ACCESS TO BASKET BASIC". The overall aim is to "analyze the average revenue and its impact on access to basic goods during the period 2014". For the present study a sample of 380 was made, from a population of 44 778 heads of household in the City of Loja. The results show that 53% of households have incomes of 2 to less than 4 SBU., Placing this percentage of the population at a medium level, followed by 25% of households receiving income from 1 to less than 2 basic wages Consolidated reaching this percentage of households in a medium low level, 10% of households receive lower incomes than 1 SBU placing them in this range of the population at a low level within the economic stratification so their income does not allow them access to cost of the basic basket. In addition 12% of higher income households 5 SBU reaching this percentage of households at a high level according to their income. KEYWORDS: Inflation, Recipients, Income, Changes in inflation, the Consumer Price Index (CPI), basic family basket, Vital food basket.